The influence of different freezing and frozen storage temperatures on Clostridium perfringens type A in raw chicken wings - Guran, Husnu Sahan; Oksuztepe, Gulsum (WFL Publisher Ltd., 2014)
Clostridium perfringens is one of the most frequently encountered anaerobic pathogen causing food poisoning in human beings. Most of the poisoning is caused by chromosomal cpe positive C. perfringenstype A. The purpose of the present work was to investigate the survival ability of chromosomal cpepositive C. perfringens type A in raw chicken wings at different freezing and frozen storage temperatures. For this purpose, chicken wings were contaminated with vegetative chromosomal cpepositive C. perfringenstype A, and then the samples were freezing and stored at -12°C± 1°C (1st group), freezing and stored at -18°C± 1°C (2nd group) and freezing at -40°C ± 1°C following stored at -18°C ± 1°C (3rd group). The number of cpe positive C. perfringenstype A in the samples at 1st group significantly decreased during the storage time (P > 0.05)and dropped below detection level (<1 log10 cfu/cm2) after 112 day of storage while the number of the pathogen in the samples at 2nd group and 3rd group decreased 2.12 and 2.05 log10 cfu/cm2, respectively. Within the 1st group found that there was significant difference days of the storage (P > 0.05), while no significant differences within the 2nd and 3rd group after the 7thday of storage (P > 0.05). These results indicated that vegetative chromosomalcpe positive C. perfringens type A inoculated onto chicken wings are able to survive for a long time at -18 °C.
Keywords: Chicken wing; Clostridium perfringens type A; Freezing; Frozen storage; Survive